Upper Limb Neural Tension and Seated Slump Tests: The False Positive Rate among Healthy Young Adults without Cervical or Lumbar Symptoms - Davis, D. Scott (Journal of Manual & Manipulative Therapy, Inc., 2008)
This study examined the false positive rate of the upper limb neural tension test (ULNTT) and seated slump test (SST) among healthy young adults with no history of cervical, lumbar, or peripheral symptoms. Eighty-four subjects (27 men and 57 women) with a mean age of 22.9 years participated in the investigation. All participants completed a screening questionnaire designed to exclude subjects with a history of cervical or lumbar spine pain or injury, or upper or lower extremity neurological symptoms. The ULNTT and the SST were performed on the left upper and lower extremity of each participant. Of the 84 participants tested, 73 (86.9%) were found to have a positive ULNTT at some point in the available range of elbow extension. Twenty-eight (33.3%) of the 84 subjects had a positive SST at some point in the available range of knee extension. The mean knee extension angle for those subjects with a positive SST was 15.1° with a 95% confidence interval (CI) of 12.3 and 19.7°. The mean elbow extension angle for those with a positive ULNTT was 49.4° with a 95% CI of 44.8 and 54.0°. The number of positive tests for both the ULNTT and the SST was found to be high in this sample of asymptomatic healthy young adults. Based on the results of this investigation, the authors suggest that the current criteria for determining a positive test for both the ULNTT and the SST should be examined using the proposed range of motion cut-off scores.